Role of HDL in neutralizing the VLDL effect on endothelial dysfunction - Zago, Valeria (2013)
It has been reported that LDL inhibits endothelium-dependent relaxation (EDR) and that HDL can neutralize this effect. However, the atherogenic properties of VLDL have been so far difficult to demonstrate. Studies on VLDL are controversial, and nothing is known about the role of HDL on potential VLDL vascular actions. We examined the effect of human VLDLs on EDR, and the role of HDL in this system.